Time-Varying Market Integration and Expected Returns in Emerging Markets - Frank de Jong; Frans A. de Roon (Tinbergen Institute, 2001)
We use a simple model in which the expected returns in emerging markets depend on their systematicrisk as measured by their beta relative to the world portfolio as well as on the level ofintegration in that market. The level of integration is a time-varying variable that depends on themarket value of the assets that can be held by domestic investors only versus the market value ofthe assets that can be traded freely. Our empirical analysis for 30 emerging markets shows thatthere are strong effects of the level of integration or segmentation on the expected returns inemerging markets. The expected returns depend both on the level of segmentation of the emergingmarket itself and on the regional segmentation level. We also find that there is significanttime-variation in the betas relative to the world portfolio because of the level of segmentation.For the composite index of the emerging markets we find an annual increase in beta of 0.09due to decreased segmentation of the emerging markets in our sample period. In terms ofexpected returns the total effect on the composite index translates into an average decreaseof 4.5 percent per annum. As predicted by our model, the noninvestable assets are moresensitive to the local and less to the regional level of segmentation than the investable assets.These conclusions do not change when using additional control variables. We do not find aclear pattern between volatility and segmentation, however.
Keywords: 330; Marktintegration; Marktsegmentierung; Schwellenländer; CAPM; Kapitalmarkttheorie; Theorie